'Getting away from it all' takes on a new meaning. - HORNER, Simon (1995)
Notes that the authorities in Suriname are keen to expand its eco-tourism sector, currently in its infancy. The case for eco-tourism is that it offers an opportunity to exploit the tropical forest which might otherwise suffer the depradations of loggers, mining enterprises and road developers.